PENGARUH BREATHING RELAXATION DENGAN TEHNIK BALLON BLOWING TERHADAP SATURASI OKSIGEN PADA PASIEN TUBERCULOSIS DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN TAHUN 2021 - Sarida Surya Manurung; Rini Panggabean; Hamonangan Damanik; Deddy Sepadha Putra Sagala (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Pulmonary Tuberculosis is a direct infectious disease caused by Tuberculosis bacteria (Mycobacterium tuberculosis), which are aerobic bacteria that can live mainly in the lungs. Physiological and psychological changes statistically are symptoms that are often experienced by tuberculosis patients which can reduce the patient's quality of life. Breathing relaxation with balloon blowing technique is a form of breathing exercise that can improve lung function. The purpose of this study was to determine the effect of breathing relaxation with the balloon blowing technique on oxygen saturation in tuberculosis patients at the Imelda General Hospital for Indonesian Workers in 2021. The population in this study was 137 people. The sampling technique in this study was accidental sampling using inclusion and exclusion criteria, thus the number of samples was 30 people. The design of this study was pre-experimental with pre-post-test one design. Data were analyzed univariately and bivariately using the Wilcoxon test. The results showed that there was a significant change in oxygen saturation before and after the intervention was given for 6 days. The results of statistical analysis showed p value = 0.01 <0.05 on the oxygen saturation variable. breathing relaxation using the balloon blowing technique can increase oxygen saturation in tuberculosis patients at IPI Medan Hospital. It is recommended for respondents to maintain oxygen saturation by doing breathing relaxation using the balloon blowing technique.